Pseudoautosomal Region 1 Overdosage Affects the Global Transcriptome in iPSCs From Patients With Klinefelter Syndrome and High-Grade X Chromosome Aneuploidies - Astro, Veronica; Alowaysi, Maryam; Fiacco, Elisabetta; Saera-Vila, Alfonso; Cardona-Londoño, Kelly J.; Aiese Cigliano, Riccardo; Adamo, Antonio (Frontiers in Cell and Developmental Biology, 2022)
Klinefelter syndrome (KS) is the most prevalent aneuploidy in males and is characterized by one or more supernumerary X chromosomes. Here, using a paradigmatic cohort of KS-induced pluripotent stem cells (iPSCs) carrying 49-XXXXY, 48-XXXY, and 47-XXY karyotypes, we identified the genes within the pseudoautosomal region 1 (PAR1) as the most susceptible to dosage-dependent transcriptional dysregulation and therefore potentially responsible for the progressively worsening phenotype in higher grade X aneuploidies. By contrast, the biallelically expressed non-PAR escape genes displayed high interclonal and interpatient variability in iPSCs and differentiated derivatives, suggesting that these genes could be associated with variable KS traits. By interrogating KS-iPSCs at the single-cell resolution we showed that PAR1 and non-PAR escape genes are not only resilient to the X-inactive specific transcript (XIST)-mediated inactivation but also that their transcriptional regulation is disjointed from the absolute XIST expression level. Finally, we explored the transcriptional effects of X chromosome overdosage on autosomes and identified the nuclear respiratory factor 1 (NRF1) as a key regulator of the zinc finger protein X-linked (ZFX). Our study provides the first evidence of an X-dosage-sensitive autosomal transcription factor regulating an X-linked gene in low- and high-grade X aneuploidies.